Investigation of Operating Parameters Influencing Electrostatic Charge Generation in Gas-Solid Fluidized Beds - Giffin, Amanda (Université d'Ottawa / University of Ottawa, 2011)
Electrostatic charge generation in gas-solid fluidized beds is a significant industrial problem. Associated problems include particle agglomeration and particle wall fouling. In the polymerization industry this may result in "sheets" of fused polymer, due to exothermic reaction causing the melting of the polymer, which can fall off and block the distributor plate disrupting fluidizing gas flow. Additionally, blockage of the catalyst feed or the polymer removal system can take place or the product can become non-uniform. All of these problems require shut-down of the reactor which results in lost production time. While this phenomena has been identified for many years, the mechanisms involved are not well understood, especially wall fouling and the distribution of charge within the bed. Isolation of individual parameters such as hydrodynamics, operating conditions, and material involved is necessary to evaluate how each parameter impacts charge generation during fluidization. In this thesis, the fluidization system consisted of a stainless steel column, two online Faraday cups, and a retractable distributor plate. This system allowed for the simultaneous measurement of charge within different regions of the bed: the entrained fine particles, the particles adhered to the column wall, and the bulk of the bed. Additionally, mass and particle size distributions were measured and images of the layer of particles adhered to the column wall were taken for comparison. This allowed for a charge distribution comparison and evaluation of wall fouling. Three different parameters were investigated: duration of fluidization, column wall material, and relative humidity of fluidizing gas. Fluidization time was studied for 15, 30, 60, 120, 180, and 360 min; relative humidity was investigated for 0%, 20%, 40%, 60%, and 80% relative humidity. Both fluidization time and relative humidity were evaluated at four different fluidization gas velocities, two each in the bubbling and slugging flow regimes. Column wall material was evaluated for a stainless steel and carbon steel column at two gas velocities, one each in the bubbling and slugging flow regimes. Fluidization time was found to influence wall fouling in the bubbling flow regime as the particle layer continued to build as fluidization progressed. In the slugging flow regime, the particle layer developed within 15 minutes of the onset of fluidization. The bubbling flow regime was shown to have a greater capacity for charge generation than the slugging flow regime. This was due to the vigorous mixing in the bubbling flow regime resulting in more particle-particle interactions. Column wall material was shown to influence wall fouling in the slugging flow regime due to the differences in surface roughness of the columns. This was due to the particle-wall contacts resulting in frictional charging which is the predominant charging mechanism in this flow regime. Charge was also impacted in the bubbling flow regime in those particles that were adhered to the column wall. Relative humidity was found to influence wall fouling at the lowest gas velocity tested. However, variations in generation of charge occurred at all fluidization gas velocities tested; the charge-to-mass ratios for the particles adhered to the column wall in the slugging flow regime decreased with high relative humidities. This was due to either the formation of a water film layer on the column wall or instantaneous surface water films on the particles throughout fluidization.
Keywords: Gas-Solid Fluidization; Electrostatics; Column Material; Fluidization Time; Relative Humidity; Charge Generation